2012
DOI: 10.1111/j.1741-3729.2012.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Financial Issues and Divorce

Abstract: Using longitudinal data from the National Survey of Families and Households and both wife‐ and husband‐reported data (N = 4,574 couples), this study examined how financial well‐being, financial disagreements, and perceptions of financial inequity were associated with the likelihood of divorce. When financial disagreements were in the model, financial well‐being was not associated with divorce. Both wives' and husbands' financial disagreements were the strongest disagreement types to predict divorce. Mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
151
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 29 publications
7
151
0
2
Order By: Relevance
“…These findings are remarkably similar to studies of heterosexual couples' relationship dissolution, which have highlighted poor communication (Rogge and Bradbury 1999), growing apart (Hawkins et al 2012), financial disagreements (Dew et al 2012), sexual incompatibility (Terling-Watt 2001), infidelity (Scott et al 2013), domestic abuse (Scott et al 2013), substance abuse (Collins et al 2007), and children with difficult characteristics (Wymbs et al 2008) as contributors of divorce. For example, Scott et al (2013) studied 52 divorced heterosexual individuals in an effort to understand perceived reasons for divorce, including identification of the "final straw."…”
Section: Research On Same-gender Parents' Relationship Dissolutionsupporting
confidence: 85%
“…These findings are remarkably similar to studies of heterosexual couples' relationship dissolution, which have highlighted poor communication (Rogge and Bradbury 1999), growing apart (Hawkins et al 2012), financial disagreements (Dew et al 2012), sexual incompatibility (Terling-Watt 2001), infidelity (Scott et al 2013), domestic abuse (Scott et al 2013), substance abuse (Collins et al 2007), and children with difficult characteristics (Wymbs et al 2008) as contributors of divorce. For example, Scott et al (2013) studied 52 divorced heterosexual individuals in an effort to understand perceived reasons for divorce, including identification of the "final straw."…”
Section: Research On Same-gender Parents' Relationship Dissolutionsupporting
confidence: 85%
“…Arguments over money has been found to be a predictor of low relationship satisfaction in marriages , and disagreement about money is a stronger predictor of divorce than any other common marital disagreement (Dew, Britt & Huston, 2012). In a study in the United States of America (USA) 51% of married couples indicated that they argue about financial issues.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies linking financial factors to marital satisfaction (e.g., Archuleta, Britt, Tonn, & Grable, 2011;Dew, 2011) and marital instability (e.g., Dew, 2009;Dew, Britt, & Huston, 2012;cf. Andersen, 2005).…”
Section: Introductionmentioning
confidence: 99%